1979
DOI: 10.1128/iai.24.1.90-93.1979
|View full text |Cite
|
Sign up to set email alerts
|

Mouse protective capabilities of Escherichia coli hybrids expressing Salmonella typhi antigens

Abstract: An Escherichia coli hybrid, F1061, expressing Salmonella typhi somatic antigens 9 and 12, and a derivative of this hybrid, E. coli hybrid WR3078, expressing the S. typhi Vi antigen in addition to somatic antigens 9 and 12, were compared with S. typhi Ty2 in experiments to test their ability, as live vaccines, to protect Swiss white mice against death from challenge with a mouse-virulent Salmonella typhimurium hybrid expressing the S. typhi antigens 9, 12, Vi, and d. When the live, vaccinating organisms were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…This importance of the 0 antigen antibodies in the protection of mice against Salmonella infection was suggested earlier by the studies of Ornellas et al (13) and has subsequently been confirmed by the work of Sevenson et al 16as well as that of Lyman et al (12). However, our studies with these S. typhimurium hybrids have also indicated that only those immunogens directed against the 0 antigens of the challenge organism are involved in the vaccine-specific protection conferred in this system; no apparent protective role has been observed for immunogens against either the Vi antigen or the flagellar antigens expressed by the challenge organism (1,(3)(4)(5). Furthermore, one of our earliest studies suggested that expression of the Vi antigen by an S. typhimurium hybrid may alter its virulence characteristics in a manner which adversely affects its ability to respond properly as a challenge organism, with the result that some vaccines protect nonspecifically against such hybrids (1).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…This importance of the 0 antigen antibodies in the protection of mice against Salmonella infection was suggested earlier by the studies of Ornellas et al (13) and has subsequently been confirmed by the work of Sevenson et al 16as well as that of Lyman et al (12). However, our studies with these S. typhimurium hybrids have also indicated that only those immunogens directed against the 0 antigens of the challenge organism are involved in the vaccine-specific protection conferred in this system; no apparent protective role has been observed for immunogens against either the Vi antigen or the flagellar antigens expressed by the challenge organism (1,(3)(4)(5). Furthermore, one of our earliest studies suggested that expression of the Vi antigen by an S. typhimurium hybrid may alter its virulence characteristics in a manner which adversely affects its ability to respond properly as a challenge organism, with the result that some vaccines protect nonspecifically against such hybrids (1).…”
mentioning
confidence: 79%
“…Second, this 0 antigen-specific protective effect is seen more clearly when a Vi-negative hybrid is employed as the challenge organism than when a Vi-positive hybrid is used (1,2). Third, the presence of the Vi antigen in the vaccine or vaccinating strain does not contribute in any observable manner to the protection conferred against a Vi-positive S. typhimurium hybrid challenge organism (1,(3)(4)(5). In addition, the present findings show that the nonspecific protective effect that vaccination with E. coli F464 engenders against a challenge with S. typhimurium hybrid H42 (an effect that we believe is associated with Vi antigen expression by H42) does not occur when the Vi-negative S. typhimurium hybrid Hi is employed in this manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations